2014
DOI: 10.3171/2014.9.focus14516
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab for glioblastoma: current indications, surgical implications, and future directions

Abstract: Initial enthusiasm after promising Phase II trials for treating recurrent glioblastomas with the antiangiogenic drug bevacizumab—a neutralizing antibody targeting vascular endothelial growth factor—was tempered by recent Phase III trials showing no efficacy for treating newly diagnosed glioblastomas. As a result, there is uncertainty about the appropriate indications for the use of bevacizumab in glioblastoma treatment. There are also concerns about the effects of bevacizumab on wound healing that neurosurgeon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 86 publications
(138 reference statements)
0
29
0
1
Order By: Relevance
“…Previous study demonstrated that although the addition of bevacizumab to standard treatment regimens did not improve OS in newly diagnosed glioblastoma, but was associated with higher rate of response and 6-month progression-free survival in recurrent glioblastoma. [ 45 ] Fountzilas et al reported that bevacizumab in combination with VPA induced a prolonged partial response in a patient with recurrent glioblastoma. [ 46 ] Our study showed VPA has no survival benefit in patient with bevacizumab, however the dose and duration of bevacizumab were not recorded, thus further detailed studies are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study demonstrated that although the addition of bevacizumab to standard treatment regimens did not improve OS in newly diagnosed glioblastoma, but was associated with higher rate of response and 6-month progression-free survival in recurrent glioblastoma. [ 45 ] Fountzilas et al reported that bevacizumab in combination with VPA induced a prolonged partial response in a patient with recurrent glioblastoma. [ 46 ] Our study showed VPA has no survival benefit in patient with bevacizumab, however the dose and duration of bevacizumab were not recorded, thus further detailed studies are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The oral alkylating agent Temozolomide (TMZ) is used as concomitant and adjuvant chemotherapy at a dose of 75 mg/m 2 daily, throughout the radiation therapy [8]. In cases of disease recurrence after this protocol, the treatment may involve a new surgery, new radiation therapy or the use of bevacizumab (antibody targeting VEGF) [9].…”
Section: Rationale For Icm In Combination Therapymentioning
confidence: 99%
“…It has obtained accelerated approval by the United States Food and Drug Administration in May 2009. [4] However, further clinical studies showed no improvement of overall survival (OS) in patients treated with bevacizumab compared to those receiving placebo, although progression-free survival (PFS) was prolonged in the bevacizumab group. [2,5,6,9]…”
Section: Introductionmentioning
confidence: 99%